953. Frailty Among People Living with HIV In Miami, A Cross Sectional Pilot Study. (31st December 2020) - Salguero, Douglas; Rodriguez, Jornan; Raccamarich, Patricia; Abbamonte, John; Pallikkuth, Suresh; Rodriguez, Allan; Pahwa, Savita; Alcaide, Maria L
Abstract: Background: Frailty, a status of high vulnerability, is a clinical syndrome associated with adverse health outcomes and characterized by a constellation of various health deficits. Although age is a major contributor of being frail, HIV infection is associated with accelerated aging, and likely contributes to frailty. This association has seldom been evaluated. This study evaluated factors associated with frailty among PWH in Miami. Methods: Cross-sectional study. Adults (> 18 years), HIV infected (HIV+) and uninfected (HIV-), virologically suppressed for at least 1 year (< 50 copies/ml). Sociodemographic factors and the self reported FRAIL scale was administered (Fatigue, Resistance or ability to climb a single flight of stairs, Ambulation or ability to walk one block, Illnesses or non-HIV associated comorbidities, and more than 5% weight Loss in the previous year). Groups were categorized base on the FRAIL scale scoring as Non-Frail (0), Pre-Frail (1-2), and Frail (3 or more). The association by Frail categories were analyze using descriptive statistics and ordinal logistical regression. Results: N (40), median age was 43 years (SD 20.6); 35% White; 20% Hispanic; 52% females; 25 (62.5%) HIV +/ 15 (37.5%) HIV -. A small number of participants reported use of tobacco 2 (5%) and alcohol 7 (18%). More than half of the participants were frail or pre- frail (18 or 45% Non-Frail, 18 or 45% Pre-Frail, and 4 or 10% Frail, and HIV+ were more likely to be pre-frail or frail than HIV-, 72% vs 26%, p = 0.019). Frail scale symptoms were common among all participants but HIV+ reported higher fatigue than HIV- (85% vs 14%, p= 0.01). On Regression analysis, both HIV status and age were significant predictors of frailty status (HIV χ2 (1) = 4.36, p = .037 and age χ2 (1) = 13.48, p < .001). When controlling for age, being HIV - on average reduced frailty by an odds of 2.16 (b = -2.164, SE = 1.04, p = .037, 95% CI [-4.2 -0.13]). When controlling for HIV status, for every one year of increase in age, the ordered log odds of being frail increased by 0.07 (b = 0.07, SE = 0.02, p < .001, 95% CI [0.03 0.1]). Conclusion: Using the FRAIL scale, a simple tool to screen for frailty, we identified high prevalence of frailty among PWH. Further studies are needed to identify the best tools to assess frailty and prevent poor health outcomes among this vulnerable population. Disclosures: All Authors : No reported disclosures